PROGRAM LATIHAN ANKLE WEIGHT TERHADAP POWER TUNGKAI PEMAIN BOLAVOLI DI UNIT AKTIVITAS BOLAVOLI UNIVERSITAS NEGERI MALANG - Dwi Yulia Safitri; Mulyani Surendra; Rias Gesang Kinanti (Jurnal Sport Science, 2017)
Abstrak: The purpose of this study was to determine the effect of ankle weight training to volleyball player’s limb power in Volleyball Activity Unit of Malang State University. The instrument used in this research is a vertical jump test. The data analysis technique used is one way varian analysis (one way anova). Based on Anova test results using one way anova show that, p experimental group = 0,007 <0,05 which means Ho rejected, while p control group = 0,858> 0,05 meaning Ho accepted. The conclusion of this research is the giving of ankle weight exercise has good effect to volleyball player's limb power in Volleyball Activity Unit of Malang State University compared to group without ankle weight training.Keywords: Volleyball, ankle weight training, limb power